Cartesiómetro o de cómo aplicar la mecánica cartesiana - Lorenzano, Pablo; Blanco, Daniel; Carman, Christian; Donolo, Ana; Federico, Lucía; Ginnobili, Santiago; Lastiri, Mariano; O 'Lery, Mercedes; Onaha, María Eugenia (Universidad Nacional de Córdoba, 2016)
Fil: Lorenzano, Pablo. Universidad Nacional de Quilmes; Argentina.